Effect of Midwifery Skills Training for Community Nurses in Handling Pregnancy in the Elderly - Siska Indrayani; Jennie Palupi; Sri Hardi Wuryaningsih; Nurseha Nurseha; Syiska Atik Maryanti (Yayasan Adra Karima Hubbi, 2024)
Late pregnancy is becoming increasingly common in modern society, causing significant health challenges. Community nurses play an important role in providing holistic care to older pregnant women. However, they often face difficulties in managing complications that may arise. Midwifery skills training can be a solution to increase the competency of nurses in handling pregnancy cases at an advanced age. This study aims to evaluate the effect of midwifery skills training on increasing the ability of community nurses to handle pregnancy at an advanced age. This research method uses a quantitative approach. Data were collected through knowledge tests before and after training as well as direct observation during clinical practice. The results of this study stated that data analysis showed a significant increase in the knowledge and skills of community nurses who took part in midwifery skills training. They demonstrate better ability to detect and manage pregnancy complications later in life, as well as provide better emotional support and education to patients. The conclusion of this study states that midwifery skills training is effective in increasing the competency of community nurses in handling pregnancies at an advanced age. Integration of this training into educational curricula and professional development programs can improve the quality of maternal care at the community level, thereby reducing the risk of complications and improving pregnancy outcomes in late life.